2019
DOI: 10.1101/555698
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of the genetic architecture underlying eye size variation withinDrosophila melanogasterandDrosophila simulans

Abstract: 1865 484191 Fax: +44 (0)1865 483242 Running title: Evolution of Drosophila eye size AbstractThe compound eyes of insects exhibit striking variation in size, reflecting adaptation to different lifestyles and habitats. However, the genetic and developmental bases of variation in insect eye size is poorly understood, which limits our understanding of how these important morphological differences evolve. To address this, we further explored natural variation in eye size within and between four species of the Droso… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(58 citation statements)
references
References 54 publications
9
49
0
Order By: Relevance
“…Therefore, our comparative morphological and mapping data strongly suggest an independent evolution of eye size in different lineages. This observation is supported by similar data obtained for two species of the melanogaster group (Gaspar et al 2020).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Therefore, our comparative morphological and mapping data strongly suggest an independent evolution of eye size in different lineages. This observation is supported by similar data obtained for two species of the melanogaster group (Gaspar et al 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Our shape analysis revealed that increased eye size was accompanied by a contraction of the interstitial head cuticle. A similar trade-off has been observed in other Drosophila species (Norry et al 2000; Posnien et al 2012; Arif et al 2013; Keesey et al 2019; Ramaekers et al 2019; Gaspar et al 2020) and it may be associated with different investment in visual or olfactory sensory perception (Keesey et al 2019; Ramaekers et al 2019). Indeed, it has been shown that a northern D. americana strain is more “visual” because it has significantly bigger eyes compared to the antennae, while D. virilis is a more “olfactory” species with smaller eyes and bigger antennae (Keesey et al 2019).…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations